Respuesta :
Answer:
(x, y) = (8, 5)
Step-by-step explanation:
The equations are:
[tex]$ -5x + 8y = 0 \hspace{20mm} \hdots (1) $[/tex]
[tex]$ - 7x - 8y = - 96 \hspace{20mm} \hdots (2) $[/tex]
Adding (1) and (2), we get:
[tex]$ - 5x - 7x + 8y - 8y = - 96 $[/tex]
[tex]$ \implies - 12x = - 96 $[/tex]
⇒ x = 8
Substituting x = 8, in Equation (1), we get:
8y = 5x
[tex]$ \implies 8y = 5(8) = 40 $[/tex]
⇒ y = 5
Therefore, the root of the equation: (x, y) = (8, 5).
Answer:
x = 8, y = 5
Step-by-step explanation:
It worked on khan